Entrevista com a Prof.a. Dr.a. Maria Celina D’Araujo - Chaves, Geovano Moreira; Rocha, Igor Tadeu Camilo; Lanari, Raul Amaro de Oliveira (Temporalidades, 2014)
Entrevista concedida à Revista Temporalidades em 3 de fevereiro de 2014.